2022
DOI: 10.3389/fphys.2022.890536
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Cardiac Autonomic Responses During Hemodialysis Measured by Heart Rate Variability and Skin Sympathetic Nerve Activity: The Impact of Interdialytic Weight Gain

Abstract: Background: Autonomic nervous regulation plays a critical role in end-stage kidney disease (ESKD) patients with cardiovascular complications. However, studies on autonomic regulation in ESKD patients are limited to heart rate variability (HRV) analysis. Skin sympathetic nerve activity (SKNA), which noninvasively reflects the sympathetic nerve activity, has not been used in ESKD patients.Methods: Seventy-six patients on maintenance hemodialysis (MHD) treatment (a 4-h HD session, three times a week) were enrolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…In 35 patients, Tong et al showed that SD of beatto-beat intervals (SDNN) and LF/HF ratio decreased significantly 3 h after the start and almost recovered 2 h after the end of the hemodialysis session [33]. In another study in 76 patients, SDNN fluctuated, LF/HF power significantly increased, while entropy decreased during hemodialysis, suggesting a possible shift toward sympathetic hyperactivity [34]. In contrast, Rubinger et al reported that LF/HF power decreased during dialysis and was significantly lower in hemodynamically unstable patients [17].…”
Section: Discussionmentioning
confidence: 99%
“…In 35 patients, Tong et al showed that SD of beatto-beat intervals (SDNN) and LF/HF ratio decreased significantly 3 h after the start and almost recovered 2 h after the end of the hemodialysis session [33]. In another study in 76 patients, SDNN fluctuated, LF/HF power significantly increased, while entropy decreased during hemodialysis, suggesting a possible shift toward sympathetic hyperactivity [34]. In contrast, Rubinger et al reported that LF/HF power decreased during dialysis and was significantly lower in hemodynamically unstable patients [17].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to predicting AF recurrence, there are new applications in neuECG, such as acting as markers of orthostatic hypotension and recurrent syncope ( 30 , 31 ), predicting the occurrence of ventricular arrhythmia in acute coronary syndrome ( 32 ), and correlating with intradialytic weight gain in patients with end-stage renal disease ( 33 ). It has also been proposed as a marker of fitness ( 34 ) and to predict neurological recovery of patients who had cardiac arrest and are undergoing therapeutic hypothermia ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the acquisition of these employed features was complicated, and it still required more other biomarkers or calculated features to improve the quantification accuracy for practical clinical applications. The SKNA had been applied to evaluate the ANS as a non-invasive method in many clinical applications (Zhang et al, 2022), and many SKNA-derived metrices (e.g., aSKNA, bSKNA) had been validated and used for ANS qualification. Nevertheless, these parameters were susceptible to noise.…”
Section: Figurementioning
confidence: 99%
“…Although these parameters can reflect the ANS changes by empirical threshold-based nerve bursts detection, the low signal-to-noise ratio of SKNA will lead to misjudgments (Xing et al, 2022a). In addition, the low amplitude SKNA signal (0.5-80 µV) is susceptible to noise, increasing the difficulty of extracting sympathetic-related information (Zhang et al, 2022). Therefore, more work is still needed to effectively analyze the autonomic nervous activity from SKNA, especially in real-time application.…”
Section: Introductionmentioning
confidence: 99%